2011
DOI: 10.1111/j.1442-2018.2011.00608.x
|View full text |Cite
|
Sign up to set email alerts
|

Jordanian acute coronary syndrome patients' learning needs: Implications for cardiac rehabilitation and secondary prevention programs

Abstract: The identification of patients' learning needs is an essential step for nurses in order to facilitate the recovery of acute coronary syndrome survivors. This study aimed to identify and prioritize the actual learning needs of these patients and to explore the differences in learning needs on the basis of sociodemographic and clinical variables. Descriptive comparative design was used, and patients' learning needs data were collected through the Patient Learning Needs Scale. The results showed that patients nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 36 publications
4
32
3
Order By: Relevance
“…It seems logical for participants to report low QoL scores in the physical domain, because of the illness-related factors mentioned above, and the fact that around 80% of the patients have never been engaged in any physical exercises. This result is supported by another Jordanian study (24), which aimed to assess the learning needs among ACS patients. Eshah (24) indicated that participants did not recognize the importance of physical exercise to improve their physical functioning and they classified it as a low priority among other needs.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…It seems logical for participants to report low QoL scores in the physical domain, because of the illness-related factors mentioned above, and the fact that around 80% of the patients have never been engaged in any physical exercises. This result is supported by another Jordanian study (24), which aimed to assess the learning needs among ACS patients. Eshah (24) indicated that participants did not recognize the importance of physical exercise to improve their physical functioning and they classified it as a low priority among other needs.…”
Section: Discussionsupporting
confidence: 70%
“…This result is supported by another Jordanian study (24), which aimed to assess the learning needs among ACS patients. Eshah (24) indicated that participants did not recognize the importance of physical exercise to improve their physical functioning and they classified it as a low priority among other needs.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…A modified Patient Learning Needs Scale (PLNS) was used in this study. It has been used previously in cardiac populations and among Arabic cardiac patients (Eshah ; You et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…Self-efficacy and self-management skills can be developed by incorporating education and counseling techniques in either individualized or group sessions and focusing on motivational strategies. [355][356][357] Applying technology through the use of the Internet and mobile phones can help provide education and trained peer support for CABG patients after surgery, even for those who are unable to access CR programs because of geographic barriers. 358,359 Finally, individual diaries have been shown to increase patient accountability for self-management of exercise activity after CR.…”
Section: Self-management Of Cardiovascular Diseasementioning
confidence: 99%